Pengaruh debt to equity ratio dan debt to asset ratio terhadap pertumbuhan laba pada perusahaan papan utama di industri property dan real estate yang terdaftar di BEI periode tahun 2017-2021 - Cahyati, Dea Afitri; Hartikayanti, Heni Nurani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to find out how partially and simultaneously influence DER and DAR on profit growth, with a total sample of 28 main board companies in the Property and Real Estate industry which are listed on the IDX for the 2017-2021 period. This study uses secondary data in the form of numbers that are processed into a statistical measurement scale it is called secondary data. Data analysis technique using multiple linear regression test. The results of the study show that partially DER has a negative and insignificant effect on profit growth, DAR has a positive and insignificant effect on profit growth, while simultaneously DER and DAR have no significant effect on profit growth in main board companies in Property and Real Estate listed on the IDX for the 2017-2021 period.